Working girl: on selling art and selling sex - Giovannitti, Sophia (Verso, 2023)
"Giovannitti argues that if we delve into our anxieties around art and sex, we can find new ways to live and spaces of freedom"--
Keywords: Bibliographie; Nettoyer

Sexual Harassment and Violence at Music Concerts and Festivals - Heen, Miliaikeala Sj.; Lieberman, Joel D. (Center for Crime and Justice Policy, 2018)
Keywords: Bibliographie; Nettoyer

Sans consentement : trente scandales sexuels qui ont changé le Québec - Morin, Michel (2024)
Depuis l'arrivée de #MoiAussi et des autres mouvements de libération de la parole, on a assisté au Québec à une succession de scandales sexuels impliquant des personnalités publiques, figures respectées et influentes qui avaient abusé de leur pouvoir, parfois des décennies durant. Michel Morin fait un pas de côté pour revisiter ces histoires encore sensibles, en portant une attention particulière à leur traitement médiatique. Avocat de formation, il se penche aussi sur le fonctionnement du système judiciaire et son impact sur le processus de dénonciation. Sans s'ériger en juge, l'auteur laisse parler les faits, bien souvent accablants, dans un essai qui permet de prendre la mesure de ce qui a été trop longtemps ignoré, voire toléré, et du chemin qui reste à parcourir.
Keywords: Bibliographie; Nettoyer

Simple Plan renvoie son bassiste de tournée suite à des allégations d’inconduites sexuelles contre lui - Bibeault, Matt (99scenes, 2020)
C’est la firme de management de Simple Plan, Coalition Music, qui a confirmé la nouvelle. Chady Awad avait justement remplacé David Desrosiers lorsque ce dernier avait pris une pause de SP pour traiter sa dépression de 2017 à 2019. Awad était également photographe et vidéaste pour Simple Plan. Simple Plan a mis fin à sa... View Article
Keywords: Bibliographie; Nettoyer

Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance - Risner, Doug; Watson, Beccy (Springer International Publishing, 2022)
Keywords: Bibliographie; Nettoyer

Not in our house Chicago Theatre Community (Not in our house Chicago Theatre Community, 2017)
making safe spaces to do dangerous work
Keywords: Bibliographie; Nettoyer

Rhetorical Constellations and the Inventional/Intersectional Possibilities of #MeToo - Bloomfield, Emma Frances (Journal of Communication Inquiry, 2019)
Keywords: Bibliographie; Nettoyer

“A Different Kind of Man”: Mediated Transgendered Subjectivity, Chaz Bono on Dancing With the Stars - Mocarski, Richard; Butler, Sim; Emmons, Betsy; Smallwood, Rachael (Journal of Communication Inquiry, 2013)
Chaz Bono’s appearance on Dancing with the Stars (DWTS) marks one of the first primetime, network appearances of a postoperative transgender person. This article deconstructs the mediated gender subjectivities of Bono as constructed by the show itself via prerecorded segments, costume and song choices, dance partner interaction, and judges’ commentaries as well as those projected by Bono during the live, unscripted portions of the show. Combining notions of the normalization of taboo sexual subjectivities through mediated contexts with lens of gender performativity, we demonstrate how transgender subjectivities are presented to a mainstream audience via such mediated choices, but also how Bono welds some agency to resist such normalization through his live performances. Bono’s appearance on DWTS stands as an important step toward acceptance of transgendered persons in mainstream society, however through a neutered, sex-free rhetoric as projected by the mediated portions of the show, his appearance is not without controversy. Additionally, we posit that Bono represents a transnormativity of a White, upper-class postoperative heterosexual male, which others all transgendered persons who fall outside of those hegemonic parallels of safe subjectivities.
Keywords: Bibliographie; Nettoyer

How is the Ballet World Including Non-Binary Dancers? - Lund, Rebekah (Dance Major Journal, 2022)
A few pioneers have shown the way, but who will follow?
Keywords: Bibliographie; Nettoyer

Unsettling homocolonial frames of remembrance: Two-Spirit and Indigiqueer interventions at the museum - Failler, Angela (Memory Studies, 2023)
This article considers a Two-Spirit and Indigiqueer protest at the Canadian Museum for Human Rights as a flashpoint that exposes problems with how memory-making institutions are incorporating lesbian, gay, bisexual, trans and queer issues into their programming and/or collections. The protest brings into relief the museum’s investment in a homocolonial framing of remembrance for the way in which the telling of lesbian, gay, bisexual, trans and queer ‘progress’ is entangled with a settler colonial political economy wherein the tokenistic inclusion of some queers into the sexual citizenry happens alongside the dispossession, devaluing and criminalizing of others. I then undertake some preliminary ‘curatorial dreaming’ upon two other interventions–commentaries uploaded to a digital story bank by a Two-Spirit and an Indigenous queer museumgoer, and the short film Woman Dress by Plains Cree artist TJ Cuthand. Along with the protest, the commentaries and the film unsettle homocolonial frames of remembrance and provide critical openings towards decolonial queer memory work at the museum.
Keywords: Bibliographie; Nettoyer

Hypermasculinity Makes the Queer Boy Faint - Alterio, Anthony M. (Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance, 2022)
Through the lens of personal experience, this chapter provides an exploration of the oft-concealed practices and hypermasculine ideals in dance education. Commercial, concert, and academic dance pedagogy continues to create and perpetuate homophobia that restricts the definition of “boy dancer” to the point of creating a false scarcity and competition to be the most cis-heteronormative male possible. Alterio argues this environment contributes to the perpetuation of discrimination against LGBTQIA+ dancers, the exclusion of non-cis boys, and lack of innovation in the field. Recommendations are offered to those interested in pushing the boundaries of performance and gender identity and a call for institutions to support this work.
Keywords: Bibliographie; Nettoyer

«Sous la ceinture»: La culture du viol, «pas une lubie de féministe» - Chabot, Kim (HuffPost, 2016)
«Sous la ceinture»: La culture du viol, «pas une lubie de féministe»
Keywords: Bibliographie; Nettoyer

Personal Safety for Dance (2022)
Personal Safety for Dance exists to develop a dance environment that is free from abuse, open, and supportive for all in dance.
Keywords: Bibliographie; Nettoyer

Je n'en ai jamais parlé à personne - Delvaux, Martine (Éditions Heliotrope, 2020)
«En octobre 2017, devant la vague de témoignages suscitée par le mouvement #moiaussi, j’ai senti une urgence : une fois sorties du silence, nous ne devions pas y retourner. C’est la raison pour laquelle j’ai lancé un appel. Ce livre est une chambre d’échos. Un chœur. Sans déesse ni héroïne en tête, des voix avancent. Nous faisons front commun.» Martine Delvaux «Je n'en ai jamais parlé à personne» : paroles recueillies et agencées par Martine Delvaux
Keywords: Bibliographie; Nettoyer

Diversity, Equity, Inclusion & Belonging Committee (ACTRA National, 2023)
ACTRA National’s Diversity, Equity, Inclusion & Belonging Committee promotes the principles concerning the casting of People of Colour, Indigenous Peoples and people with disabilities. The best initiatives are driven by members. We can better shape initiatives to support you by getting to know our membership and understanding your experiences. We welcome your input and your […]
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Commande un Angelot (2021)
« Le protocole d’accréditation Commande un Angelot a été conçu afin de s’attaquer aux violences à caractère sexuel dans les bars et les événements festifs ou sociaux. Celui-ci vise à prévenir ces situations et à venir en aide aux personnes en difficulté. Le Collectif social, un organisme sans but lucratif qui souhaite déployer et soutenir la réalisation d’initiatives de nature communautaire ou sociale qui répondent aux besoins des communautés étudiantes des établissements d’enseignement supérieur, est derrière ce projet. »
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Dénoncez un incident sur le plateau (ACTRA Montreal, 2024)
Grâce aux rapports anonymes, nous sommes informés des problèmes au fur et à mesure qu’ils surviennent. Il est possible de rester anonyme, mais il est préférable de laisser vos coordonnées pour que nous puissions vous contacter. Nous ne donnerons jamais suite à une réclamation sans votre consentement!
Keywords: Bibliographie; Nettoyer

Coordonnateur·rice·s de l'intimité - ACTRA Montréal (ACTRA Montreal, 2024)
Les coordonnateurs d'intimité sont des spécialistes de la production qui planifient, supervisent et coordonnent les scènes intimes filmées.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

The Story of Jane Doe: A Book About Rape - Doe, Jane (Vintage Canada, 2004)
Keywords: Bibliographie; Nettoyer

Workplace Sexual Harassment 30 Years on: A Review of the Literature - McDonald, Paula (International Journal of Management Reviews, 2012)
Despite its proscription in legal jurisdictions around the world, workplace sexual harassment (SH) continues to be experienced by many women and some men in a variety of organizational settings. The aims of this review article are threefold: first, with a focus on workplace SH as it pertains to management and organizations, to synthesize the accumulated state of knowledge in the field; second, to evaluate this evidence, highlighting competing perspectives; and third, to canvass areas in need of further investigation. Variously ascribed through individual (psychological or legal consciousness) frameworks, sociocultural explanations and organizational perspectives, research consistently demonstrates that, like other forms of sexual violence, individuals who experience workplace SH suffer significant psychological, health- and job-related consequences. Yet they often do not make formal complaints through internal organizational procedures or to outside bodies. Laws, structural reforms and policy initiatives have had some success in raising awareness of the problem and have shaped rules and norms in the employment context. However, there is an imperative to target further workplace actions to effectively prevent and respond to SH.
Keywords: Bibliographie; Nettoyer

Les dénonciations publiques d'agressions sexuelles : du mauvais usage de la présomption d’innocence - Lessard, Michaël (Revue Femmes et Droit, 2017)
French Abstract: Lorsqu’une victime dénonce son agresseur sur la place publique, certaines personnes tentent de la réduire au silence en invoquant le droit à la présomption d’innocence. Ce fut particulièrement évident en 2014, lors du mouvement #AgressionNonDénoncée ; ce le fut encore à l’automne 2015, alors que des femmes autochtones de Val-d’Or dénonçaient les agressions sexuelles commises à leur endroit par des policiers ; ce le fut aussi en 2016 à l’occasion de la dénonciation du député Gerry Sklavounos par Alice Paquet ; et l’argument légaliste réapparaît ainsi périodiquement sur la scène publique. Pourtant, peut-on vraiment bâillonner une victime en mettant de l’avant les droits de son agresseur ? L’auteur estime qu’il s’agit là d’un mauvais usage de la présomption d’innocence. Dans ce texte, il explique que la présomption d’innocence doit être replacée dans son contexte juridique. Le droit à la présomption d’innocence est un principe fondamental qui protège les accusés contre le pouvoir punitif de l’État. Il trouve uniquement application dans le processus pénal et n’est pas conçu pour être employé sur la scène publique. De plus, l’auteur explique que, dans le cadre du processus pénal, la présomption d’innocence favorise la création d’un espace de discussion où les parties peuvent débattre de la culpabilité. Pourtant, lorsqu’elle est invoquée sur la scène publique, elle ne fait que placer les victimes dans un processus violent de remise en question de leur crédibilité, tout en protégeant les agresseurs. Son invocation crée une atmosphère qui décourage les dénonciations. Le débat public dévie, laissant peu de place pour critiquer nos systèmes de plaintes dysfonctionnels et la culture du viol. En ce sens, la présomption d’innocence n’est pas invoquée afin d’établir un dialogue constructif, mais plutôt pour faire taire les critiques.English Abstract: When a victim reports her aggressor publicly, some people try to silence her voice under the guise of the right to the presumption of innocence. This was especially remarkable in 2014, within the movement #AgressionNonDénoncée; and again in the fall of 2015, when Val-d’Or Indigenous women reported being sexually assaulted by police. It was also the case in 2016 when Alice Paquet denounced Member of Provincial Parliament Gerry Sklavounos, and the legal argument thus periodically reappears on the public stage. However, can we really silence a victim by advancing the rights of her aggressor? The author believes that this is a case of inappropriate use of the presumption of innocence. In this text, he explains that the presumption of innocence must be placed in its legal context. The right to the presumption of innocence is a principle that protects litigants against the punitive power of the state. Its sole application belongs in the criminal process, and it was not designed to be used as such on the public stage. In addition, the author explains that, at the heart of the criminal process, the presumption of innocence promotes the creation of a discussion space where all parties may debate the guilt. However, when it is invoked in the public sphere, it only places the victims in an aggressive process of questioning their credibility while protecting the aggressors. Its invocation creates a climate that deters denunciations of sexual assaults. The public debate deviates, leaving little room to criticize our dysfunctional complaint systems and rape culture. In that sense, the presumption of innocence is not invoked in order to establish a constructive dialogue, but it has the effect of shutting down its critics. In this article, the author explains why the right to the presumption of innocence must not be engaged in this way in the public sphere.
Keywords: Bibliographie; Nettoyer

Gay men in the performing arts: Performing sexualities within ‘gay-friendly’ work contexts - Rumens, Nick; Broomfield, John (Organization, 2014)
Building on emerging research on ‘gay-friendly’ organizations, this article examines if and how work contexts understood and experienced as ‘gay-friendly’ can be characterized as exhibiting a serious breakdown in heteronormativity. Taking the performing arts as a research setting, one that is often stereotyped as ‘gay-friendly’, and drawing on in-depth interview data with 20 gay male performers in the UK, this article examines how everyday activities and encounters involving drama school educators, casters and peers are shaped by heteronormative standards of gay male sexuality. Adopting a queer theory perspective and connecting with an emergent queer theory literature in organization studies, one concern articulated in this article is that heteronormative constructions of gay male sexualities constrain participants’ access to work; suggesting limits to the abilities and roles gay men possess and are able to play. Another concern is that when gay male sexualities become normalized in performing work contexts, they reinforce organizational heteronormativity and the heterosexual/homosexual binary upon which it relies. This study contributes towards theorizing the heteronormative dynamics of ‘gay-friendly’ places of work, arguing that gay male sexualities are performatively instituted according to localized heteronormativities which reinforce contextually contingent, restrictive heteronormative standards of gay male sexuality which performers are encouraged to embody and perform both professionally and personally.
Keywords: Bibliographie; Nettoyer; Raphaël

Il était une fois... de trop - Institut national de l'image et du son. (2024)
Une formation pour prévenir le harcèlement en culture.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Sexual Harassment in Display Work: The Case of the Modeling Industry - Crowley, Jocelyn Elise (Gender & Society, 2021)
Keywords: Bibliographie; Cultural industries; Display work; Fashion; Informal industries; Modeling industry; Myriam; Nettoyer; Power dynamics; sexual harassment

How Independent Contractors Respond to Sexual Harassment: The Case of the Modeling Industry - Crowley, Jocelyn Elise (Employee Responsibilities and Rights Journal, 2022)
Sexual harassment continues to be a problem that most commonly affects women in the United States workforce today. While there are legal and organizational remedies available, most of these mechanisms for redress only exist for workers in traditional employeremployee contexts. Independent contractors, self-employed workers who represent a growing number of labor force participants in this economy, can therefore only use informal means of addressing sexual harassment. This study used grounded theory methods to analyze 88 separate narratives of sexual harassment from 70 fashion models, an overwhelmingly female set of independent contractors currently operating in the American economy. The aim of the analysis was to understand the mix and meaning behind the use of informal strategies—more specifically confrontation versus non-confrontation—in response to this sexual harassment. Notably, models most often confronted the perpetrators of harassment. Critically, however, those models who chose non-confrontation did not minimize the abuse that they faced. Instead, they either saw themselves as powerless or engaged in self-blame when faced with harassment on the job.
Keywords: Bibliographie; Confrontation; Fashion industry; Independent contractors; Models; Myriam; Nettoyer; Sexual harassment

Challenging gendered power: How sexual harassment perpetrators respond to victim confrontation - Crowley, Jocelyn Elise (Gender, Work & Organization, 2023)
Sexual harassment is a problem that continues to plague mostly women in the American workforce today. One tool that victims can use in these situations is confrontation, either through verbal or physical means. Yet, understudied to this point is how perpetrators respond to confrontation, which is highly salient as to whether this is an effective tool for victims. This study uses grounded theory methods to analyze 31 accounts of sexual harassment from within the fashion industry that recorded perpetrators' responses to victim confrontation to clearly unwanted, abusive behavior. I argue that specific features of the fashion industry, or a “display work culture,” embolden perpetrators to effectively thwart any type of confrontation. Indeed, this study finds that these predominantly male perpetrators of sexual harassment moved to reassert their dominant position over their female victims in the moment of confrontation, immediately after being confronted, and even later, well beyond confrontation, as they aimed to reestablish normal business practices as usual. This research thus dispels a significant sexual harassment myth that victims working within this culture are able to stop perpetrators simply by speaking up and/or fighting back and points to the need for the development of sexual harassment theory to incorporate work culture-related risk factors and remedies.
Keywords: Bibliographie; Myriam; Nettoyer; confrontation; display work culture; fashion industry; perpetrators; sexual harassment

Title IX, Esports, and #EToo - Stoever, Jane K (The George Washington Law Review, 2021)
As colleges and universities increasingly award video gaming scholarships, field competitive esports teams, construct esports arenas in the centers of campuses, and promote student interaction through gaming, schools should anticipate the sexual cyberviolence, harassment, and technology-enabled abuse that commonly occur through gaming.
Keywords: Bibliographie; Irina; Nettoyer

Gendered Barriers In The Gaming Industry - Singh, Tanya (Journal of Sports Law, Policy and Governance, 2020)
As of 2019, there are an estimated 2.5 billion garners globally. Roughly half of all garners are female. Despite the figures, there is a serious underrepresentation of female gainers in the professional gaming and game development community. It is thus important to examine the underlying causes hindering equally capable female gainers and game developers from pursuing a serious career in gaming, at par with their male counterparts.In this article, the authorexamines the impact of the culturalassociationof games with the male demography, stereotypes andstructuralbarrierslimiting women from realizing theirfullpotential, female representation in video games and workplace, pervasive misogyny and sexual harassment of women across all levels in the industry, and lastly, the steps that can be taken to better the status quo in favour of women.
Keywords: Bibliographie; Irina; Nettoyer

Speaking in Public: What Women Say about Working in the Video Game Industry - De Castell, Suzanne; Skardzius, Karen (Television & New Media, 2019)
Since the 1990s, conversations about the dearth of women working in the video game industry have centered on three topics: (1) ways to draw more women into the field, (2) the experiences of women working in the industry, and (3) the experiences of those who once worked in the industry but left. Although there has been considerable research on the conditions and occupational identities of video game developers, less scholarly attention has been devoted to women in gameswork, the barriers/obstacles and challenges/opportunities they face, and how they talk about their experiences. This article offers a feminist approach that demonstrates how discourse focused on affect can be reread as intimately related to silences about power and how the rhetorical constraints that public speech imposes upon what can be said about “women in games” aid us in understanding what might remain unspoken, and why.
Keywords: Bibliographie; Irina; Nettoyer

Exploring Vicarious Liability to Remedy the #E-Too Movement - Hewson, Eloise (York Law Review, 2022)
The esports, or competitive video gaming, industry is an exciting area of economic and cultural growth. Gaming can facilitate interpersonal connection, shared problem-solving, and creativity. Players may purchase a game, watch a streamer play it online, join an online gaming community, attend a tournament, compete professionally, or find employment in game development or a related field. The gaming industry generates enormous economic value and employs tens of thousands of people in the UK alone. However, the esports sector does not extend its benefits equally. Women are regularly verbally harassed in video games, countless women have been groped at esports events, women have been raped by professional players, underage fans have been groomed. Abuse is endemic to online gaming communities.
Keywords: Bibliographie; Irina; Nettoyer

Winnipeg comedy club defends decision to book Louis C.K. despite sexual misconduct - Caruk, Holly (CBC News, 2019)
An American comedian and actor who admitted to sexual misconduct will take the stage at a Winnipeg comedy club next week but not everyone is lining up for tickets.
Keywords: Bibliographie; Nettoyer; Sophie-Anne

ReadTheCode.ca - Canadian Creative Industries (2017)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

#ThisIsArtSchool Is Exposing Allegations Of Racism & Sexual Abuse In Montreal Universities - Elliot, Teddy (MTL Blog, 2020)
As stories of racism and discrimination towards Black, Indigenous, and people of colour continue to dominate public discourse, more and more shocking allegations come to light about the lived experiences of systemic racism.
Keywords: Bibliographie; Nettoyer

Designing Women: Learning from Feminist Legacies and the Women-In-Games Movement - Schoemann, Sarah (Georgia Institute of Technology, 2021)
In 2019 the video games industry was rocked by a slew of high-profile sexual harassment and assault allegations that some called the #MeToo movement of the games world, but to many these revelations came as no surprise. From the 2004 EA Spouse controversy to the 2014 #Gamergate harassment campaign the games industry has long been known for harboring an at times toxic atmosphere of exploitation and discrimination. This project looks at a handful of Women-In-Games organizations that set out to change the experience of women in the industry by helping newcomers to gain high tech skills and to supporting early career professionals through mentorship and community building. Along the way, it combines the study of these Women-In-Games organizations with a years-long collaboration bringing video games to the US' oldest feminist bookstore, Charis Books & More in Atlanta, GA. Through examining the work and values of two types of organizations devoted to women's equality, one a historic feminist movement-building space and the others, contemporary interventions into the professional games and tech industry, this study asks the questions "What can the Women-In-Games movement learn from the rich history of feminist organizing at spaces like Charis?" "Can games play a part in feminist movement building?" and "What does the future of feminist organizing look like in the games industry?”
Keywords: Bibliographie; Irina; Nettoyer

Let Her Play: A report on gender-based violence in video games - Mettler, Kirsten (Embodied: The Stanford Undergraduate Journal of Feminist, Gender, and Sexuality Studies, 2022)
Globally, video games are a $152 billion industry, and approximately 3.1 billion people, or 40% of the population, are players (Ingersoll & Anti-Defamation League, 2019, Price, 2020). Gaming is a huge industry, and it’s only getting bigger. Unfortunately, women and other historically marginalized groups often face staggering levels of harassment and violence in these communities. This report aims to explore the issue of gender-based violence in video games by analyzing contributing factors and proposing gaming company interventions.
Keywords: Bibliographie; Irina; Nettoyer; esports

We protect animals well": A structural approach to abusive conduct within circus schools - Matthis, Rosa (Linköping University, 2021)
This master thesis investigates abusive conduct in circus schools. Focus is put on the management level in order to achieve and provide knowledge of measures and attitudes related to prevention. Th ...
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Are Female Clowns Politically Incorrect? A Case Study on Female Clowns’ Political Engagement at the 7th “Esse Monte de Mulher Palhaça” festival in Rio de Janeiro - Cézard, Zed (Cadernos de Arte e Antropologia, 2020)
By linking the notion of politics with clown practices played out during the biennial festival «Esse Monte de Mulher Palhaça» in Rio de Janeiro (2018), dedicated specifically to female clowns, the relations between politics and feminism are raised, as well as the question of the place of clowns and women within the social system in which they act. In addition to reassessing the concept of politics through this new field of application, looking at what artistic practices convey or denounce as inequalities, allows us to identify politicized and political social elements. The private sphere, the power relations, the importance of gender, and the body and sexuality as treated in the festival’s performances raise political issues. We are lead to think of the phenomenon of Brazilian female clowns as a political space of claims, in particular feminist ones, and a resistance to dominant sexist normativity.
Keywords: Bibliographie; Brazil; Nettoyer; Sophie-Anne; female clowns; feminism; activism; politics

The impact of intervention measures on sexual harassment in the film and television industry - Eng, Ben; McKinney, Ralph; Shao, Lawrence (Journal of International Management Studies, 2019)
Since 2017, increased sexual harassment incidents have been reported in Hollywood; yet, little guidance has been offered on how organizations, which are informally governed by their network members, can effectively reduce sexual harassment. Building upon the theory of network governance, this paper suggests social mechanisms, which are used to coordinate and safeguard exchanges between Hollywood organizations, are more effective at reducing incidents of workplace sexual harassment than traditional strategies. These social mechanisms direct change to the macroculture through collective sanctions that damage the perpetrators reputation and restrict access to network opportunities. In essence, perpetrators become toxic assets that Hollywood avoids and this avoidance is similar to economic sanctions that can deter sexual harassment.
Keywords: Bibliographie; Irina; Nettoyer

#TimesUp on Individual Litigation Reform: Combatting Sexual Harassment through Employee-Driven Action and Private Regulation - Dugan, Natalie (Columbia Journal of Law and Social Problems, 2020)
Keywords: Bibliographie; Irina; Nettoyer

Sexual Harassment in the Creative Industries: Tolerance, Culture and the Need for Change: Sexual harassment in the creative industries - Hennekam, Sophie; Bennett, Dawn (Gender, Work & Organization, 2017)
The economic, social and cultural contributions of the creative industries are essential elements of many societies and their governments’ policies. However, there is growing evidence that precarity, competition and lack of regulation within these industries is exacerbating inequalities with respect to gender, race and class. With a focus on gender and sexual harassment among female workers, this study involved 32 in-depth interviews with women working in the Netherlands’ creative industries. Data were analyzed using content analysis. Findings suggest that sexual harassment is prevalent, and many women considered it to be part of their occupational culture and career advancement. Four factors inﬂuenced this phenomenon: competition for work; industry culture; gendered power relations; and the importance of informal networks. Implications include the need for a climate of non-tolerance, sector-speciﬁc research and guidelines, sensitivity training and further work with unions and professional associations to provide worker protection strategies traditionally undertaken by organizations. The article concludes that effective sexual harassment prevention requires action at the individual, educational, sectoral and governmental levels, beginning with public conversations to convey the message that sexual harassment is never acceptable.
Keywords: Bibliographie; Irina; Nettoyer

The impact of #MeToo in the South African film and television industry, within a historical framework - Majiba, Ntsika (Université de l'Afrique du Sud, 2022)
The study is a history project and is concerned with tracking the impact of #MeToo in the South African Film and Television industry in South Africa. Its main premise were the findings made public by a South African organization, Sisters Working in Film and Television (SWIFT) in 2017, that found that sexual harassment in the television and film industry was not just a norm but a crisis. The core focus of the study was on the development and impact of the #MeToo movement, which entailed investigating the manner in which women reacted to the hashtag (#MeToo), the reaction of their male counterparts, as well as the reaction and actions taken by the various bodies, institutions and organisations in the Film and Television industry, which included; broadcasters and production houses alike. This study begins by giving a concise background of the movement by firstly, historicising various female-led movements and comparing and contrasting them with the rise of digital movements or digital activism. The historicisation involves a brief comparison of past and present women-led activism, as well as a brief review of other hashtags like #AmINext and #Enough, on which #MeToo has had an influence. It goes on to investigate the development of #MeToo movement and to discuss the responses of the industry and individuals to the movement. The study embarked on a data collection quest by interviewing eleven female television and film practitioners in South Africa. Their ages ranged from 20 to 55. The findings of the research revealed that female practitioners were still being harassed post #MeToo, although subtly. The lack of unity amongst women in the sector was cited as one of the reasons behind the ongoing harassment. Gender parity and equity was also still lacking in the South African television and film industry. This study emerged in the midst of activism and scholarship seeking to unravel the norms of South African sexual harassment and rape culture against women. Thus, the study focused on the changes and transformations brought about by the hashtag within the industry. With South Africa’s historical background and the current circumstances around Gender Based Violence (GBV), this study was concerned with tracking whether or not digital activism had in some way been able to aid change and transformation. In particular, this study looked at the impact of the MeToo phenomenon on the women in the industry, the extent to which it empowered them, what they began to say and how they began to act. The study also explored South Africa’s ‘rape culture’ as South Africa has been proclaimed the ‘worlds rape capital’. It reflected on the colonial rule as the perpetuation of patriarchy and male entitlement over female bodies. Patriarchy in the industry was also confirmed by the findings and through data analysis, as one of the key factors in the emergence of #MeToo in South Africa, and in the utilisation of the hashtag by women in the sector to speak up against sexual harassment.
Keywords: Bibliographie; Irina; Nettoyer

Gender Equality in British Film-making: Research, Targets, Change - Cobb, Shelley; Williams, Linda Ruth (Women in the International Film Industry: Policy, Practice and Power, 2020)
In October 2017, the British Film Institute declared that it would commit to specific targets for gender equality and diversity in key production roles on films with support from the Film Fund. This decision by the BFI to set targets, arguably, did not come just from their own diversity and inclusion goals. Activist film-makers had previously called for targets for the Film Fund, especially for women directors. This chapter will give an accounting of the current state of gender (in)equality in the UK industry by: outlining new research that has clarified the stagnant inequality in the UK film industry; articulating the key role of a network of activist groups (that include researchers, professional and campaigning bodies, exhibitors and film-makers) to bring attention to the problem; putting pressure on the film industry and public bodies; and summarising institutional responses to that pressure since 2016, with a critical analysis of the potential and limits of the BFI’s relatively recently implemented diversity and equality targets.
Keywords: Bibliographie; Irina; Nettoyer

Sexual violence and nightlife: A systematic literature review - Quigg, Zara; Bigland, Charlotte; Hughes, Karen; Duch, Mariangels; Juan, Montse (Aggression and Violent Behavior, 2020)
Preventing and responding to sexual violence in nightlife settings is increasingly of global concern. The goal of this article was to identify and summarise academic studies on nightlife-related sexual violence. Specifically, to explore the nature, extent and consequences of, or associations with nightlife-related sexual violence, and interventions to prevent and respond. Of the 61 studies identified, 29 explored or reported on the nature of nightlife-related sexual violence, 22 provided information on extent, 38 on associations, and 19 on prevention and response. The majority of studies had been implemented in the past ten years (2009–2018) and in high-income countries. The review illustrates that nightlife-related sexual violence is pervasive, with lifetime prevalence reaching over 50% amongst numerous study samples. Studies suggest that a combination of factors at an individual, relationship, and community/environmental level is associated with nightlife-related sexual violence. No studies directly explored consequences, and few studies evaluated prevention and response approaches. Globally, further research is required to understand nightlife-related sexual violence, and inform the development of prevention programmes across all but particularly low and middle-income countries. Critically, interventions aimed at preventing and responding to nightlife-related sexual violence require thorough evaluation, with findings disseminated in both lay and academic literature.
Keywords: Bars; Bibliographie; Nettoyer; Nightlife; Prevention; Rape; Sexual; Violence

Sexual harassment and violence at Australian music festivals: Reporting practices and experiences of festival attendees - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (Australian & New Zealand Journal of Criminology, 2020)
Despite the well-documented under-reporting of sexual violence, to date, no research has considered reporting practices within the specific context of music festivals. Drawing on 16 in-depth interviews with victim-survivors, this article examines survivors’ experiences of (non)reporting sexual violence in festival settings. We argue that while some barriers to reporting are shared across contexts, others play out in context-specific ways. Our research argues that the liberal, often transgressive culture of music festivals, combined with site-specific policing practices and spatial context, creates unique impediments to reporting with particular implications in responding to, and aiming to prevent, sexual violence at music festivals.
Keywords: Bibliographie; Camille; Nettoyer

Laughter from the Sidelines: Precarious Work in the Canadian Comedy Industry - Trusolino, Madison (Creative Industries in Canada, 2022)
Creative Industries in Canada is a foundational text that encourages students to think critically about creative industries within a Canadian context and interrogate the current state and future possibilities of the industry. While much of current creative industries literature concerns the United Kingdom, the United States, and Asia, this text captures the breadth of how Canadian industries are organized and experienced, and how they operate.This ambitious collection aims to guide students through the current landscape of Canadian creative industries through three thematic sections. “Production” collects chapters focused on how national discourses and identities are produced through creative industries and the tensions that exist between policy and media. “Participation” explores how we engage with these industries in different roles: as consumer, creator, policy-maker, and more. “Pedagogies” explores how education impacts inclusion and visibility in creative industries.Truly intersectional, Creative Industries in Canada provides students with practical industry knowledge and frameworks to explore the current state of the field and its future. With a broad application to many undergraduate programs, this text is a must-read resource for those pursuing media studies, arts management, creative and cultural industries studies, communications, and arts and humanities.
Keywords: Bibliographie; Business & Economics / Industries / Media & Communications; Nettoyer; Social Science / Media Studies; Sophie-Anne

Sexual Violence and Gender Equality in Grassroots Music Venues: How to Facilitate Change - Hill, Rosemary Lucy; Megson, Molly (IASPM Journal, 2020)
Sexual violence in the music industry is known to impact negatively on women’s participation. We examine how grassroots venues and promoters can implement changes to tackle sexual violence and work towards gender equality. We draw on UK-based, impact-focused research which sought to raise awareness of sexual violence, and to facilitate anti-violence changes within organisations. We find that working across a city’s music scene and engaging with oversight organisations such as local authorities can aid in persuading venues and promoters to seek training. However, for individuals leading on changes, personal experiences of sexual violence as a victim/survivor or bystander are important factors in their decision. We conclude that men in the music industry need to become more aware of the need for change, and willing to act on that awareness; and that more women need to own, manage, and run venues and events.
Keywords: Bibliographie; Gender; Nettoyer; live music; music industry; music venues; prevention; sexual violence

Resilience & Melancholy: Pop Music, Feminism, Neoliberalism - James, Robin (John Hunt Publishing, 2015)
When most people think that “little girls should be seen and not heard,” a noisy, riotous scream can be revolutionary. But that’s not the case anymore. (Cis/Het/White) Girls aren’t supposed to be virginal, passive objects, but Poly-Styrene-like sirens who scream back in spectacularly noisy and transgressive ways as they “Lean In.” Resilience is the new, neoliberal feminine ideal: real women overcome all the objectification and silencing that impeded their foremothers. Resilience discourse incites noisy damage, like screams, so that it can be recycled for a profit. It turns the crises posed by avant-garde noise, feminist critique, and black aesthetics into opportunities for strengthening the vitality of multi-racial white supremacist patriarchy (MRWaSP). Reading contemporary pop music – Lady Gaga, Beyonce, Calvin Harris – with and against political philosophers like Michel Foucault, feminists like Patricia Hill Collins, and media theorists like Steven Shaviro, /Resilience & Melancholy/ shows how resilience discourse manifests in both pop music and in feminist politics. In particular, it argues that resilient femininity is a post-feminist strategy for producing post-race white supremacy. Resilience discourse allows women to “Lean In” to MRWaSP privilege because their overcoming and leaning-in actively produce blackness as exception, as pathology, as death. The book also considers alternatives to resilience found in the work of Beyonce, Rihanna, and Atari Teenage Riot. Updating Freud, James calls these pathological, diseased iterations of resilience “melancholy.” Melancholy makes resilience unprofitable, that is, incapable of generating enough surplus value to keep MRWaSP capitalism healthy. Investing in the things that resilience discourse renders exceptional, melancholic siren songs like Rihanna’s “Diamonds” steer us off course, away from resilient “life” and into the death.
Keywords: Bibliographie; Music / History & Criticism; Nettoyer; Philosophy / Social